2011
DOI: 10.2511/rpsd.36.1-2.62
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Evidence-Based Practice in Teaching Science Content to Students with Severe Developmental Disabilities

Abstract: A comprehensive review of the literature was conducted for articles published between 1985 and May 2009 to (a) examine the degree to which science content was taught to students with severe developmental disabilities and (b) and evaluate instructional procedures in science as evidence-based practices. The review was organized by a conceptual model developed for science content. Seventeen experiments were analyzed for research quality where science content was taught to this population; 14 of these studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 38 publications
4
112
0
4
Order By: Relevance
“…Inquiry-based science has been proposed as the preferred means to teach science content to all students (Knight et al in press;Spooner et al 2010). Research has shown that students with ASD have difficulty using background knowledge to comprehend abstract information (Wahlberg and Magliano 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Inquiry-based science has been proposed as the preferred means to teach science content to all students (Knight et al in press;Spooner et al 2010). Research has shown that students with ASD have difficulty using background knowledge to comprehend abstract information (Wahlberg and Magliano 2004).…”
Section: Discussionmentioning
confidence: 98%
“…In a comprehensive review, Spooner et al (2010) found 17 studies related to science. While these studies provide some evidence that students with developmental disabilities can learn science content, much more research is needed to develop effective interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Yardımcı teknoloji (assistive technology), öğretim teknolojisi (instructional technology), öğrenme teknolojisi (assistive learning technology), bilgi ve iletişim teknolojisi (information and communication technology), bilgisayar destekli öğretim (computer assisted instruction) kavramlarıyla alanyazında sıkça karşılaşılmaktadır (Liu, Wu ve Chen, 2013;Spooner, Knight, Browder, Jimenez ve DiBiase, 2011) Teknoloji, farklı kavramlarla tabir edilse de günümüz dijital teknolojilerinin sağladığı olanakların en iyi şekilde kullanılarak zihin yetersizliği olan öğrencilerin eğitimlerine katkıda bulunması en temel amaçtır. Bu araştırmada yazarlar kavram karmaşasını engellemek amacıyla ileri düzey (dijital) teknolojik araçları nitelemek amacıyla teknoloji terimini kullanmayı hedeflemiştir.…”
Section: Introductionunclassified
“…There is limited research in the areas of reading, mathematics, and science for students with severe developmental disabilities, although that research base is growing (e.g., Browder et al, 2010;Spooner et al, 2011). This growing research demonstrates how to create meaningful extensions to the general curriculum and how to teach this academic content.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…In a comprehensive review of science content instruction for students with moderate/severe developmental disabilities, Spooner, Knight, Browder, Jimenez, and DiBiase (2011) found 17 studies; however, only 14 of these met criteria for evidence-based practice (Horner et al, 2005). Spooner et al's review provided support for using systematic instruction, such as task analysis and systematic prompting with feedback, to teach science content to students with severe disabilities.…”
mentioning
confidence: 99%